The effects of a novel bicarbonate loading protocol on serum bicarbonate concentration: a randomized controlled trial - Adam Marcus; Amerigo Rossi; Andrew Cornwell; Steven A. Hawkins; Nazareth Khodiguian (Taylor & Francis Group, 2019)
Background Previous studies have shown that sodium bicarbonate ingestion may enhance intense exercise performance, but may also cause severe gastrointestinal distress. The purpose of this study was to determine whether a modified sodium bicarbonate (SB) ingestion protocol would elevate serum bicarbonate concentration more than previous methods without causing gastrointestinal distress. Methods In randomized order, seven (5 men, 2 women) elite middle-distance runners ingested either placebo, Modified SB (600 mg·kg− 1 over 19.5 h), or Acute SB (300 mg·kg− 1) in opaque gelatin capsules. Baseline and post-ingestion blood samples were analyzed for bicarbonate, pH, sodium, hematocrit, and lactate. Repeated measures ANOVA (2 time points × 3 conditions) were analyzed to determine differences in serum bicarbonate, lactate, sodium, blood pH, and hematocrit. Gastrointestinal distress was assessed via self-report on a Likert scale of 1-10. Simple (condition) and repeated (time) within-participant contrasts were used to determine the location of any statistically significant main and interaction effects (p ≤ 0.05). Results Both Modified SB (7.6 mmol·L− 1, p < 0.01) and Acute SB (5.8 mmol·L− 1, p < 0.01) increased serum bicarbonate concentration compared to the placebo (p ≤ 0.05). Post-ingestion serum bicarbonate concentration was significantly higher for the Modified SB (34.7 ± 2.2 mmol·L− 1, 28.0% increase) trials than the Acute SB (33.5 ± 2.0 mmol·L− 1, 20.9% increase) trials (p = 0.05). There was no reported severe GI distress in the Modified SB trials, but two cases in the Acute SB trials. Conclusions Modified SB elevated serum bicarbonate concentration more than Acute SB, without any severe gastrointestinal side effects. Consequently, it is recommended that future experimentation involving SB by researchers and athletes use the novel ingestion protocol described in this study due to its potential for improved effectiveness and reduced gastrointestinal impact. Trial registration ClinicalTrials.gov , NCT03813329 . Registered 23 January 2019 - Retrospectively registered,